Does trade liberalization lead to specialization in dirty industries? A CGE assessment for Kenya - Muthuthi, Charles Kariuki (AUC Knowledge Fountain, 2017)
The dearth of empirical evidence across developing countries on whether trade liberalization would lead a country to specialize in dirty industries to exploit its comparative advantages in trade, motivates this thesis. The thesis uses the case of Kenya, - a lower-middle income country with the largest economy in Eastern Africa- to investigate two fundamental questions: (i) will Kenya's realization of its comparative advantages in trade, relative to those of its neighbors, heighten the risk of specialization in dirty production? and (ii) will Kenya's trade competitiveness be adversely impacted by its implementation of an environmental tax that directly targets polluting energy inputs? Compared to a 2009 base-run, the impact of three alternative ex-ante policies were quantitatively evaluated: further trade liberalization, alone; pollution abatement, alone; and joint implementation of these policies. A static computable general equilibrium (CGE) model for Kenya, that is theoretically founded on the tradition of CGE models for open developing economies by the World Bank (Dervis, et al., 1982), was developed to investigate these fundamental issues. Deepening Kenya's trade liberalization, alone, was found to have beneficial effects on output, with the risk that the country could intensify its specialization in dirty industries. In comparison, an environmental policy in the form of a tax on energy inputs, alone, reduced pollution in energy-intensive industries, but was costly in terms of falling output. Potential worsening of Kenya's environmental situation might, nevertheless, be mitigated without adversely affecting output through a mix of policy interventions. In conclusion, even if political commitments for a cleaner environment were in place in Kenya, which is far from certain, further trade liberalization without concrete policy interventions to abate industrial pollution, might create or exacerbate environmental degradation.